Peran Kemitraan dalam Optimalisasi Satuan Pendidikan Non Formal Berbasis Program Pelatihan di SKB Negeri Surabaya dengan Politeknik Indonesia - Hidayat, Wahyu Pratama Nasrul; Rosyanafi, Rofik Jalal (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
This study aims to: describe the role of the partnership in optimizing the training program-based Non-Formal Education Unit at the SKB Negeri Surabaya with the Politeknik Indonesia and describe the implementation of the training program-based Non-Formal Education Unit partnership at SKB Negeri Surabaya with the Politeknik Indonesia. This research is a qualitative research using a descriptive approach. The subjects of this study were the Head of the SKB Negeri Surabaya, the Tutor of the SKB Negeri Surabaya, and training resource persons from the Politeknik Indonesia. Collecting data using in-depth interviews, participant observation, and documentation. Researchers are the main research instrument assisted by interview guidelines. Data analysis techniques performed were data collection, data reduction, data presentation and conclusion. After that, the validity of the data is carried out to increase the degree of trust in the data that has been obtained in the field by triangulating sources. The role of the partnership between the two parties SKB Negeri Surabaya and the Indonesian Polytechnic seeks to define new breakthroughs in order to increase the prestige and quality of education. The implementation of the partnership between the Surabaya State SKB and the Indonesian Polytechnic is in the form of a computer training program for SKB students.